The Difficult Client-Acceptance Decision in Canadian Audit Firms: A Field Investigation - GENDRON, YVES (Contemporary Accounting Research, 2001)
Auditing is often depicted in scientific and professional literature as being subject to conflicting forces, such as mechanization versus flexibility, and professionalism versus commercialism. This paper examines how auditors actually make the client-acceptance decision in the midst of these forces. The investigation was conducted via a field study at three Big 6 firms located in Canada. The results show that in all firms the client-acceptance decision process in action is largely flexible, being characterized by a high degree of informal communication and the adaptation of the client-acceptance written policies and decision aids to circumstances. Furthermore, while commercialism in one firm (A) has a significant influence on the decision process, in the two other firms (B and C) the decision process is mostly consistent with professionalism. This result conflicts with the concerns that North American regulators have recently expressed about auditors' professionalism.